Telaah Buku Teks Mata Pelajaran Bahasa Jawa SMA Wiyata Basa Jawa ‘WIBAWA’ Berdasarkan Diagram FRY - Wulan, Sri Hertanti; Suwarna, Suwarna; Nurhidayati, Nurhidayati; Rubiyanto, Yayan (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2020)
This study will reveal the quality of the textbooks used in DIY for high school students. From this research, the textbook standard will become a reference so that it can be used to achieve the goals of regional language education that have been mandated in the curriculum. This is a descriptive study. The data were collected from the WIBAWA book "Wiyata Basa Jawa". The research instrument consisted of WIBAWA textbook assessment instrument with Fry Graph instruments/indicators. WIBAWA textbook readability was 66.67%, while 33.33% of the book did not meet legibility. The 33.33% unacceptability does not mean completely unacceptable, but there are parts that are too easy and some parts that are too difficult, so it needs to be revised.